2008
DOI: 10.1177/0734016808320709
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of Prior Record, Race, Ethnicity, and Policy

Abstract: Using sentencing data from 1994 to 2002, spanning two different sentencing policies, this study examines the complex relationship between felony offenders' prior record, race/ethnicity, current offense, and sentencing outcomes. Expanding on past research, this study incorporates multiple dimensions of prior record and analyzes the differential impact of these dimensions across race/ethnicity and offense type. Unlike previous research, the current study examines these complex effects across different sentencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
0
26
0
2
Order By: Relevance
“…Criminal justice involvement earlier in life can have persistent impacts on one's penal career (Crow, 2008; Kutateladze, Andiloro, Johnson, & Spohn, 2014; Mueller‐Smith & Schnepel, 2019; Pager, 2003; Wooldredge, Frank, Goulette, & Travis, 2015). First, earlier convictions often become permanent records and accumulate into criminal history.…”
Section: Crime–punishment Wave and Cohort Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Criminal justice involvement earlier in life can have persistent impacts on one's penal career (Crow, 2008; Kutateladze, Andiloro, Johnson, & Spohn, 2014; Mueller‐Smith & Schnepel, 2019; Pager, 2003; Wooldredge, Frank, Goulette, & Travis, 2015). First, earlier convictions often become permanent records and accumulate into criminal history.…”
Section: Crime–punishment Wave and Cohort Effectsmentioning
confidence: 99%
“…Criminal history consistently and strongly predicts the severity of sanctions for a new crime later in the life (Kleck, 1981; Spohn, 2000; Steffensmeier, Ulmer, & Kramer, 1998). Police, prosecutors, or judges can react more punitively to offenders with prior convictions at each stage of a criminal proceeding (Crow, 2008; Kutateladze et al., 2014; Wooldredge et al., 2015). At the system level, “penal code escalations or risk classification algorithms” in the sentencing process often depend on criminal conviction history (Mueller‐Smith & Schnepel, 2019, p. 19).…”
Section: Crime–punishment Wave and Cohort Effectsmentioning
confidence: 99%
“…The final set of input variables is representative of well-known risk factors for recidivism (Bushway and Piehl, 2007;Crow, 2008) and has been used in risk assessment tools since 1928 (see, for example, Borden (1928), Hinojosa et al (2005), Berk et al (2006) and Baradaran (2013)). They include (a) information about prison release in 1994 (e.g.…”
Section: Deriving Input Variablesmentioning
confidence: 99%
“…Our court observations suggested that these linkages are not intended to mitigate offender responsibility but to show how systemic factors embedded within shared Aboriginal history contribute to criminal records and over-incarceration; ideally, these linkages can help disrupt this cycle one case at a time. This process differs from traditional court practices, where factors such as a lengthy criminal history are generally used to demonstrate the “riskiness” of an offender and to justify detention or incarceration (Crow 2008; Roberts 1997). When an offender’s behaviour is located within the broader experiences of victimization and disadvantage, it becomes possible to consider the extent to which he or she has been placed at risk and victimized; this moves the analysis beyond a narrow focus on his or her level of risk or risk of recidivism.…”
Section: Reconstituting the Legal Subjectmentioning
confidence: 99%